Les collections permanentes du Louvre et l’exposition de l’art contemporain - Ariane Lemieux (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Contemporary art pieces within the path of ancient art history’s  permanent exhibitions has become a known occurrence for visitors.  Some even mention it as a musicological phenomenon revealing a generalized interest for contemporary art. But, more than that, it reveals the museums new reality of ending the permanency to the benefit of the event, asserts cultural programing and the public.